Impact of Women Entrepreneurship on Economic Growth: A Study of Selected SME’s in Imo State - Ekwutosi, Ozims; Achiole, Ayozie Emmanuel; Kodichimma, Udokwu Nnamdi (Research Parks Publishers, 2024)
This study has examined the impact of women entrepreneurship on economic growth income. The specific objectives of the study were to examine the impact of women entreprenuership on employment generation, to investigate the impact of women entreprenuership skill and learning on wealth creation, and to ascertain the impact of women social status on community and social development. The study adopted survey design approach, the total population was 450, using Taro Yamene formular the sample size of 212 was derived, however the total number of questionnaires returned was 201 which was used for the analysis. the questionnaire was subjected to supervisor’s corrections so as to achieve face and content validity. The test-retest approach was employed to ascertain the reliability coefficient. The researcher calculated the Spearman's rank correlation coefficient, designated as r, which above 0.5, so affirming the instrument's reliability using the statistical program SPSS version 20.0. The non-parametric Chi-Square test and Analysis of variance (ANOVA) statistical tools were used to test the hypotheses at 0.05 level of significance. The key findings of the study shows that women entrepreneurship has impacted on employment generation. Also, that women entrepreneurship skill and learning has impacted on wealth creation. The study further discovered that women social status has impacted on the community/social development. The report suggests that the government implement measures to promote women as sources or drivers of entrepreneurship to support economic growth. As the majority of women entrepreneurs develop their businesses as micro and small enterprises, often viewing them as family enterprises likely stemming from their motivation to generate income for family sustenance they require marketing, financial, and managerial skills for the effective management of these entrepreneurial operations. Women social status should not be abused as most people even in community might use it to allocate resources unequally thereby introducing inequality and injustice in the distribution of resources especially in our communities.